Branched polyethyleneimine functionalized tin(IV)-porphyrinic complex: Synthesis, characterization and application towards acid blue 25 adsorption from water - Raoudha Soury; Mahjoub Jabli; Mabrouka El Oudi; Ashanul Haque; Khalaf M. Alenezi; Ahmed Al Otaibi; Fahad Abdulaziz; Amor Bchetnia (Results in Chemistry)
In the present work, we report the synthesis, characterization and anionic dye adsorption application of a polyethyleneimine (PEI) functionalized (5,10,15,20 tetraphenyl porphyrinato) tin(IV) dichloride Sn(TPP)(Cl2). The adsorbent [Sn(TPP)(Cl2)]-PEI was prepared via a swift protocol and characterized extensively using multi-nuclear spectroscopic techniques including the 1H NMR, FT-IR and UV–Vis spectroscopic techniques. X-ray diffraction (XRD) data confirmed that the addition of PEI to the Sn-porphyrin complex did not affect its crystallinity. On the other hand, scanning electron microscopy (SEM) analysis indicated that the morphological characteristics of Sn(TPP)Cl2 and [Sn(TPP)(Cl2)]-PEI were different. The prepared material was tested for its ability to adsorb Acid Blue 25, an anionic dye, from water. The adsorption results showed a significant enhancement in the adsorption capacity of the resulting material. Under optimized conditions (pH = 5, time = 60 min., and T = 295.15 K), the adsorption capacity of [Sn(TPP)(Cl2)]-PEI was 208 mg/g while it was 14 mg/g for [Sn(TPP)(Cl2)]. The fitting of the adsorption data indicated that the process followed pseudo-second-order and Langmuir equations. Overall, we reported a simple and cost-effective method for efficient adsorbent for removing anionic dyes from contaminated water.